Propuesta para el mejoramiento de procesos productivos en la empresa Inarecrom S.A. - Caguana Paucar, Vladimir Fabricio (2021)
The purpose of the following investigation was to deliver to the company Inarecrom SA, multiple improvements in its production processes within its finishing lines, and also to the administration area, the results will be reflected both in quality, reduction of production costs and of both human and technological resources available to the company, giving as an opening to a more optimal production chain and with it that the company can have a better response to the current moments that are required in its environment. The improvements to the finishing lines will positively help each station or workstation, and incidentally the administrative worker staff to manage and control the internal factors of each area, thereby giving a better response to internal and external customers, with products that an adjusted quality index and improving the increase in productivity. This study to improve production processes will help control and optimize both inputs and resources that are used daily. The impact of this research on Inarecrom SA is positive since it allows it to differentiate itself from other companies that do not have this type of study, setting a standard with respect to competitiveness both nationally and internationally and giving a broader focus on how to help tools of the Industrial Engineering career leading to meeting objective goals through the union of practice and work method, in the same way to deepen the learning obtained for decision making, execution and control without forgetting aptitude as a human attitude.